Long‐Term Outcomes of Pediatric Living Donor Liver Transplantation in Japan: An Analysis of More Than 2200 Cases Listed in the Registry of the Japanese Liver Transplantation Society. Issue 7 (24th May 2013) - Kasahara, M.; Umeshita, K.; Inomata, Y.; Uemoto, S.; ,
Abstract The Japanese Liver Transplantation Society (JLTS) was established in 1980 in order to characterize and follow trends in patient characteristics and graft survival among all liver transplant patients in Japan. This study analyzed the comprehensive factors that may influence the outcomes of pediatric patients who undergo living donor liver transplantation (LDLT) by evaluating the largest cohort in the world. Between November 1989 and December 2010, 2224 pediatric patients underwent LDLT in Japan. There were 998 male (44.9%) and 1226 female donors (55.1%) without donor mortalities related to transplant surgery. There were 946 male (42.5%) and 1278 female (57.5%) recipients with a median age of 4.0 years (range: 13 days to 17.9 years). Cholestatic liver disease was the leading indication for LDLT (n = 1649; 76.2%), followed by metabolic disorders (n = 194; 8.7%), acute liver failure (n = 192; 8.6%) and neoplastic liver disease (n = 66; 3.0%). The 1‐, 5‐, 10‐ and 20‐year patient survival rates were 88.3%, 85.4%, 82.8% and 79.6%, respectively. Blood‐type incompatibility, recipient age, etiology of liver disease and transplant era were found to be significant predictors of overall survival. We are able to achieve satisfactory long‐term pediatric patient survival outcomes in the JLTS series without compromising the living donors.